Korelasi antara Pembiasaan Istighosah dan Pembiasaan Sholat Dhuha Terhadap Akhlak Peserta Didik MI Nurul Huda Kwangsen Jiwan Kabupaten Madiun - Ririn Puji Lestari (BASICA, 2025)
This study aims to analyze the correlation between the habitual practice of istighosah (communal supplication) and Dhuha prayer and the moral character (akhlaq) of students at MI Nurul Huda Kwangsen Jiwan, Madiun Regency. The study employs a descriptive quantitative approach with a correlational survey design. The population consisted of 92 students, with a sample of 62 respondents. Data collection techniques included questionnaires, observation, and documentation. Data analysis utilized descriptive statistics, normality tests, linearity tests, and multiple linear regression. The results indicate that the habitual practice of istighosah has a significant effect on students' moral character, with a significance value of 0.016 (< 0.05) and a calculated t-value of 2.475. The habitual practice of Dhuha prayer also significantly affects students' moral character, with a significance value of 0.000 (< 0.05) and a calculated t-value of 13.313. Simultaneously, the habitual practices of istighosah and Dhuha prayer significantly influence students' moral character, with an R-Square value of 0.754, indicating a 75.4% contribution to the formation of the students' moral character. The findings demonstrate that the habitual practice of religious activities in the madrasah plays a crucial role in shaping the character and moral conduct of students.